Preoperative Hypertension: Incidence, E?ect on Perioperative Risks and Outcome - Mamta Jain; Anish Kumar Singh; Vandna Arora; Sanjay Johar; Jatin Lal; Teena Bansal (Academia Anesthesiologica International, 2020)
Background: Hypertension (HTN) is the most frequent preoperative abnormality detected in surgical patients. Its high prevalence necessitates an analysis of its severity and the associated perioperative risks. There is always a controversy about whether to postpone elective surgery given poorly controlled HTN or not. The present study aimed to observe the incidence of HTN in pre-surgical patients, associated co-morbidities   and end-organ damage, perioperative risks and outcome. Subjects and Methods: After approval from ethical committee, in this prospective observational study 1180 adult surgical patients were assessed for HTN. Patients found to be hypertensive were then categorized as known hypertensive, HTN detected at PAC clinic and hypertensive on day of operation. These patients were further investigated for end-organ damage. Hemodynamic changes at the time of intubation, any intraoperative complications and post-operative morbidity and mortality were also observed. Results: The incidence of HTN was 9.2%, out of these 47.7% were known hypertensive, 27.5% had raised blood pressure on admission and 24.7% were detected for the first time in the preoperative room. In hypertensive patients, haemodynamic fluctuations were more during the intraoperative period. Eight patients (7.4%) had fresh, transient (lasted<10minutes) ECG changes (five had ischemic changes and three had arrhythmias) that required no treatment. Five (4.6%) patients were postponed due to hypertension. Conclusion: HTN is a frequently encountered abnormality seen among presurgical patients and many patients remain undetected till the time of surgery. During surgery, these preoperatively detected hypertensive patients have more swings in BP as compared to known hypertensive patients who are on regular treatment. However, stage 1 & 2 HTN alone is not found to be associated with increased risk and data from the present study indicates that stage 3 HTN without end-organ damage can undergo minor surgeries safely.